Effect of Sacha Inchi Oil on Human Blood Pressure and Lipid Profile: A Preliminary Study in Malaysia - En, Cheong Yi; Binti Udin, Nur Ayuni; Vanoh, Divya A/P; Leng, Soo Kah (Jurnal Gizi dan Pangan, 2024)
This uncontrolled pre-post study aimed to assess changes in blood lipid profiles and blood pressure resulting from a 2-month consumption of Sacha Inchi Oil (SIO) (Plukenetia volubilis). Investigating the effects of SIO on Malaysians is essential for tailoring interventions to the local context, considering genetic, cultural, and dietary differences. A total of 13 adult participants, comprising 8 males and 5 females aged 35 to 74 years old, took part in this intervention study. Each participant was instructed to consume 2 softgels daily, with each softgel containing 530 mg of SIO. Blood lipid profiles and blood pressure were measured at baseline and at the end of the 2-month period, utilizing venipuncture for blood tests and a sphygmomanometer for blood pressure assessment. The results indicated a significant reduction in Systolic Blood Pressure (SBP) levels following SIO supplementation (2 softgels daily) (p<0.05). However, there were no notable improvements in Diastolic Blood Pressure (DBP), Total Cholesterol (TC), Low-Density Lipoprotein Cholesterol (LDL-C), High-Density Lipoprotein Cholesterol (HDL-C), and Triglycerides (TG) after the 2-month supplementation. In conclusion, the daily supplementation of 2 softgels of SIO (1,060 mg) for 2 months demonstrated a beneficial effect on blood pressure, particularly in reducing SBP. These findings serve as preliminary data for future research into the potential health benefits of SIO in the Malaysian population.